PENGARUH PENAMBAHAN MINYAK JAHE SEBAGAI ANTIOKSIDAN ALAMI DALAM PENINGKATAN KUALITAS MINYAK IKAN PATIN (Pangasius hypophthalmus) - Yan Hendrika; Azlaini Yus Nasution; Vonny Kurnia Utama; Sherly Putri Arsila (FORTE JOURNAL, 2023)
The high nutritional content in catfish oil can be a rich source of omega-3 fatty acids, which function in the development of the child's brain. However, the high fatty acid content causes fish oil to become more susceptible to oxidation during the storage process, which can be prevented by adding antioxidants. This study aims to determine the quality of catfish oil after adding ginger oil as an antioxidant. The method used is the titration method to determine the peroxide value and the number of free fatty acids. The results obtained for fish oil peroxide with the addition of ginger oil on days 0, 7, and 14 were 1.58 meq/kg, 1.58 meq/kg, and 2.11 meq/kg. The free fatty acid values of catfish oil added to ginger oil on days 0, 7, and 14 were 0.57%, 0.58%, and 2.11%, respectively. These results show that this value still meets IFOS standards, and ginger oil can act as an antioxidant.